PERLINDUNGAN HAK CIPTA TERHADAP PEMBAJAKAN FILM DALAM PLATFORM LAIN TANPA IZIN - Asti Giri Anjani; Geza Arditya; Mey Lia Sari; Aisyah Resta Melati; Agvianto Perdawan (Cahaya Ilmu Bangsa, 2024)
Film piracy on digital platforms has become an increasingly troubling problem for copyright holders. With the increasing accessibility of the internet, copyrighted films can easily be distributed illegally on various platforms without permission. This article investigates the challenges faced by copyright holders in protecting their works from piracy on digital platforms. This research uses legal analysis methods and literature studies to identify the main obstacles and possible solutions to overcome this problem. The research results show that copyright protection against film piracy requires a holistic approach, involving collaboration between government, industry and digital platforms. In addition, the implementation of copyright protection technology and education to the public about the impact of piracy on the film industry is also needed. This article also reviews various legal and technological strategies that can be used to reduce film piracy on digital platforms. Thus, this article provides important insights for copyright holders, policy makers, and legal practitioners in their efforts to protect film copyrights from piracy on digital platforms.